Synthesis of novel 3-benzylxanthine derivatives - Aleksandrova, K. V.; Vasylyev, D. A.; Krisanova, N. V.; Александрова, Катерина Вячеславівна; Васильєв, Денис Андрійович; Крісанова, Наталія Вікторівна (Одеса : ГО «Південна фундація медицини», 2021)
Chemical compounds, which contain heterocyclic core characterize to be very promising structures in drug discovery. A survey of literature exposes the biological properties of such constituents including hypoglycemic, anticancer, antioxidant, anti-inflam-matory, and other important pharmacological activities. Therefore, special attention should be derived to 3-benzyl-xanthine core, which play an important role in the biochemical processes on plant and animal cells. Previous studies showed that among N– and C-substituted xanthines there are various substances with good biological effects (antimicrobial, antihypertensive, analeptic, psychotropic and anticancer). In medical practice there are many effective xanthine derivatives (diprophylline, 6-mercap-topurine, trental etc.) that employ successfully.